2014
DOI: 10.7567/jjap.53.05fw07
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and optical properties of CuInSe2–ZnSe system

Abstract: CuIn) 1%x Zn 2x Se 2 (ZCISe) (0.0 : x : 1.0) in the CuInSe 2 -ZnSe system were successfully synthesized by mixing the elemental powders and postheating at 600 °C. X-ray diffraction analysis showed that the lattice constants of ZCISe shortened with increasing Zn content. From the Rietveld refinements of X-ray diffraction data, we found that crystal structure changes from a chalcopyrite-type [I 42d (No. 122)] structure at 0.0 : x : 0.2 to a zinc blende-type [F 43m (No. 216)] structure at 0.6 < x : 1.0. ZCISe w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…The incorporation of Zn in the CuInSe 2 structure caused a decrease in the volume of the elementary lattices (Table 1) because the radius of the Zn 2+ ion (radius = 0.74 Å) is smaller than that of In 3+ (radius = 0.81 Å). These results are in agreement with previous results in literature, where it was observed [12] that CuInZnSe peaks were shifted to higher diffraction angles with the incorporation of Zn. The incorporation of Zn in the CuInSe2 structure caused a decrease in the volume of the elementary lattices (Table 1) because the radius of the Zn 2+ ion (radius = 0.74 Å) is smaller than that of In 3+ (radius = 0.81 Å).…”
Section: Structural Properties Of Cuin 1-x Zn X Se 2 Nanopowderssupporting
confidence: 94%
See 1 more Smart Citation
“…The incorporation of Zn in the CuInSe 2 structure caused a decrease in the volume of the elementary lattices (Table 1) because the radius of the Zn 2+ ion (radius = 0.74 Å) is smaller than that of In 3+ (radius = 0.81 Å). These results are in agreement with previous results in literature, where it was observed [12] that CuInZnSe peaks were shifted to higher diffraction angles with the incorporation of Zn. The incorporation of Zn in the CuInSe2 structure caused a decrease in the volume of the elementary lattices (Table 1) because the radius of the Zn 2+ ion (radius = 0.74 Å) is smaller than that of In 3+ (radius = 0.81 Å).…”
Section: Structural Properties Of Cuin 1-x Zn X Se 2 Nanopowderssupporting
confidence: 94%
“…The incorporation of Zn in the CuInSe2 structure caused a decrease in the volume of the elementary lattices (Table 1) because the radius of the Zn 2+ ion (radius = 0.74 Å) is smaller than that of In 3+ (radius = 0.81 Å). These results are in agreement with previous results in literature, where it was observed [12] that CuInZnSe peaks were shifted to higher diffraction angles with the incorporation of Zn.…”
Section: Structural Properties Of Cuin 1-x Zn X Se 2 Nanopowderssupporting
confidence: 94%
“…Some of the structural properties of the [CuInSe 2 ] 1‐ x [ZnSe] 2 x system have been studied previously . It has been shown that for low ZnSe concentrations ( x < 0.1), a CIZSe phase with chalcopyrite (CH) structure is stable at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the structural properties of the [CuInSe 2 ] 1-x [ZnSe] 2x system have been studied previously. [6][7][8][9] It has been shown that for low ZnSe concentrations (x < 0.1), a CIZSe phase with chalcopyrite (CH) structure is stable at room temperature. A solid solution with sphalerite (SP) crystal structure exists for the high ZnSe concentration (x > 0.35).…”
mentioning
confidence: 99%
“…Then the Zn is completly incorporated into the CZTISe alloy maybe because of the formation of other compounds such as CuInZn 2 Se instead of ZnSe. Because of similar lattice parameters of CuInZn 2 Se 4 and CZTSe[16,17,18], the 220/204 diffraction peaks also overlap. Hence, the separation of the CZTSe and CuInZn 2 Se 4 diffraction peaks in XRD is even less developed than the separation of the ZnSe and CZTSe diffraction peaks.…”
mentioning
confidence: 99%